The relationship between night eating behavior, gastrointestinal symptoms, and psychological well-being: insights from a cross-sectional study in Türkiye - Emine Merve Ekici; Özge Mengi Çelik; Ziya Erokay Metin (Journal of Eating Disorders)
Abstract Background This cross-sectional study aimed to address the gap in understanding how night eating behavior impacts gastrointestinal health and psychological well-being in adult populations. Method This descriptive and cross-sectional study was conducted with 1372 adults aged 19–65 between September 2023 and November 2023. The research data were collected with the help of a web-based survey form (Google form) created by the researchers using the snowball sampling method. The demographic characteristics (sex, age, education level, marital status, income status), eating behaviors (number of main meals and snacks), and anthropometric measurements (body weight and height). Gastrointestinal symptoms observed in individuals were evaluated with the Gastrointestinal Symptom Rating Scale. The Night Eating Questionnaire (NEQ) was used to quantify the severity of night eating syndrome, and The Psychological Well-Being Scale was used to measure psychological well-being. All analyses were performed using the Statistical Package for the Social Sciences (version 27.0) software. Results A statistically significant negative correlation was found between the Psychological Well-Being Scale total score and Gastrointestinal Symptom Rating Scale subdimensions (r=-0.067, r=-0.067, r=-0.109, r=-0.068, r=-0.129, respectively). Also, a statistically significant negative correlation was found between the Psychological Well-Being Scale total score and the Night Eating Questionnaire total score (r=-0.287) (p < 0.05). Conclusion This study found a relationship between night eating syndrome, psychological well-being, and gastrointestinal symptoms. Nutritional strategies for night eating syndrome, an eating disorder, may have important consequences on the psychological well-being of individuals with night eating. Our study highlights the significant relationships between night eating behavior, gastrointestinal symptoms, and psychological well-being, suggesting that night eating may contribute to both physical and mental health challenges.